Yanṭiq: A proposed concept in philosophy of islamic communication - Muslih, Mohammad; Latifi, Yulia Nasrul; Taqiyuddin, Muhammad (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose – This study aims to understand the nature of speaking from the perspective of philosophical anthropology and communication ethics, with particular emphasis on its role in reflecting human identity as al-insān al-nāṭiq (the rational and speaking being). Method – This study employed a reflective-philosophical approach, analyzing classical and contemporary perspectives on language philosophy, communication ethics, and the degradation of speech in the context of social media and instant expression culture. The method consisted of a critical literature review and conceptual analysis rather than empirical sampling. Result – The results showed that speaking is not merely a biological function or impulsive response but a conscious act that integrates reason, emotion, and moral responsibility. In the modern era, however, speech tends to lose depth, control, and ethical awareness, leading to risks such as misinformation, social fragmentation, and symbolic violence. Implication – This study suggests the need to revive reflective, ethical, and intentional communication practices to strengthen social harmony, protect human dignity, and ensure that speech continues to serve as a medium of truth and genuine dialogue. Originality/Value – This research provides a novel reinterpretation of the act of speaking within the framework of Islamicate philosophical anthropology and communication ethics, offering a critical alternative to contemporary communication practices dominated by speed and superficiality. *** Tujuan – Penelitian ini bertujuan untuk memahami sifat berbicara dari perspektif antropologi filosofis dan etika komunikasi, dengan penekanan khusus pada perannya dalam mencerminkan identitas manusia sebagai al-insān al-nāṭiq (makhluk rasional dan berbicara). Metode – Penelitian ini menggunakan pendekatan reflektif-filosofis, menganalisis perspektif klasik dan kontemporer tentang filsafat bahasa, etika komunikasi, dan degradasi berbicara dalam konteks media sosial dan budaya ekspresi instan. Metode ini terdiri dari tinjauan literatur kritis dan analisis konseptual, bukan pengambilan sampel empiris. Hasil – Hasil menunjukkan bahwa berbicara bukan sekadar fungsi biologis atau respons impulsif, melainkan tindakan sadar yang mengintegrasikan akal, emosi, dan tanggung jawab moral. Namun, dalam era modern, ucapan cenderung kehilangan kedalaman, kontrol, dan kesadaran etis, yang berpotensi menimbulkan risiko seperti disinformasi, fragmentasi sosial, dan kekerasan simbolis. Implikasi – Studi ini menyarankan perlunya menghidupkan kembali praktik komunikasi yang reflektif, etis, dan sengaja untuk memperkuat harmoni sosial, melindungi martabat manusia, dan memastikan bahwa ucapan tetap berfungsi sebagai medium kebenaran dan dialog yang sejati. Orisinalitas/Nilai – Penelitian ini menawarkan reinterpretasi baru tentang tindakan berbicara dalam kerangka antropologi filosofis Islam dan etika komunikasi, memberikan alternatif kritis terhadap praktik komunikasi kontemporer yang didominasi oleh kecepatan dan kedangkalan.